Whole body precooling attenuates the extracellular HSP72, IL-6 and IL-10 responses after an acute bout of running in the heat - Lee, B. J.; Clarke, N. D.; Hankey, J.; Thake, C. D. (Journal of Sports Sciences, 2018)
The impact of whole-body precooling on the extracellular heat shock protein 72 (eHSP72) and cytokine responses to running in the heat is undefined. The aim of this study was to determine whether precooling would attenuate post-exercise eHSP72 and cytokine responses. Eight male recreational runners completed two 90-minute bouts of running at 65% O2max in 32 ± 0.9°C and 47 ± 6 % relative humidity (RH) preceded by either 60-minutes of precooling in 20.3 ± 0.3°C water (COOL) or 60 min rest in an air-conditioned laboratory (20.2 ± 1.7°C, 60 ± 3% RH; CON). eHSP72, TNF-a, IL-6, IL-10 IL-1ra were determined before and immediately after exercise. The elevation in post-exercise eHSP72 was attenuated after COOL (+0.04 ± 0.10 ng/mL) compared to CON (+ 0.29 ± 0.26 ng/mL;P < 0.001). No changes in TNF-a were observed at any stage. COOL reduced the absolute post-exercise change in IL-6 (P = 0.011) and IL-10 (P = 0.03) compared to CON. IL-1ra followed this trend (P = 0.063). A precooling-induced attenuation of eHSP72 and proinflammatory cytokines may aid recovery during multi-day sporting events, but could be counterproductive if a training response or adaptation to environmental stress is a desired outcome.